1998
DOI: 10.1364/ao.37.008382
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia detection and monitoring with photofragmentation fluorescence

Abstract: Excimer laser fragmentation-fluorescence spectroscopy is an effective detection strategy for NH(3) in combustion exhausts at atmospheric pressure and high temperatures. Two-photon photofragmentation of NH(3) with 193-nm light yields emission from the NH(A-X) band at 336 nm. There are no major interferences in this spectral region, and the sensitivity is at the parts per billion (ppb) level. Quenching of the NH(A) state radical by the major combustion products is measured and does not limit the applicability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…18 Excimer laser fragmentation-fluorescence spectroscopy (ELFFS) has been used to detect toxic metals such as Pb, Cr, and Ni, 19 chlorinated hydrocarbons, 20,21 and ammonia at atmospheric pressure. 22 Alkali species have also been detected using ELFFS in pressurized boilers. 23,24 Raiche et al 25 have suggested that photofragmentation fluorescence might provide a useful diagnostic for acetylene detection in flames.…”
Section: Introductionmentioning
confidence: 99%
“…18 Excimer laser fragmentation-fluorescence spectroscopy (ELFFS) has been used to detect toxic metals such as Pb, Cr, and Ni, 19 chlorinated hydrocarbons, 20,21 and ammonia at atmospheric pressure. 22 Alkali species have also been detected using ELFFS in pressurized boilers. 23,24 Raiche et al 25 have suggested that photofragmentation fluorescence might provide a useful diagnostic for acetylene detection in flames.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic resonances for NH 3 are located in the vacuum ultraviolet, making it difficult to measure NH 3 using conventional laser techniques . Photofragmentation of NH 3 and subsequent NH fluorescence detection has been applied as a means to circumvent this problem . Another option is to probe the electronic resonances using two‐photon processes, which has been demonstrated with laser‐induced fluorescence, polarisation spectroscopy and four‐wave mixing techniques .…”
Section: Introductionmentioning
confidence: 99%
“…The PF/FD technique has shown promise for qualitative and quantitative analysis in a variety of applications, including, for example, the detection of vaporous hydrogen peroxide, 10 monitoring of gas-phase alkalis in coal plant exhaust to reduce fouling, [11][12][13][14] quantification of lead (in both particulate and vaporous form) as an environmental pollutant, 15 detection of the photochemical smog/acid rain contributing species NO 2 and NO, 16 environmental monitoring of chlorinated hydrocarbons, 17 and analysis of atmospheric ammonia. [18][19][20][21] Photofragmentation has also been used for the detection and quantification of several types of particulate species, such as the air pollutants ammonium nitrate and ammonium sulfate, 22 carbonaceous particles and soot generated by combustion, 22,23 and a variety of sodium-containing aerosol particles. [24][25][26] Like many laser spectroscopic techniques, PF/FD offers significant advantages over traditional off-line methods of chemical analysis in that it provides nearly instantaneous results with a high degree of species differentiation.…”
Section: Introductionmentioning
confidence: 99%